(untitled) (Journal of Management and Social Sciences, 2024)
Of the 7.7 billion current world population, the Muslims account for 1.8 billion representing 24.1 percent. According to Mickeal Lipka et al. Islam (2017) is the world’s fastest growing world religion. In his postulation, Muslims will grow more than twice as fast as the overall world population between 2015 and 2060 and in the second half of this century will likely surpass Christianity as the world’s largest religion. While the world’s population is projected to grow 32 percent in coming decades, the Muslim population is expected to increase by 70 percent from 1.8 billion in 2015 to nearly 3 billion in 2060, representing 31.1 percent which will be 3 in 10 of the world’s population.